Effect of the microstructure of graphitic boron nitride on the kinetics of the formation of boron nitride high-pressure phases. Issue 4 (April 2019) - Schimpf, C.; Schwarz, M.R.; Lathe, C.; Kroke, E.; Rafaja, D.
Abstract: Three types of hexagonal boron nitride (h-BN) with graphitic crystal structure having different microstructures were subjected to high pressures (HP) and high temperatures (HT), and the kinetics of the phase transitions to the sp 3 -hybridized phases (w-BN, c-BN) was studied using in situ synchrotron diffraction. The analysis of the phase transformation kinetics revealed the transformation paths and activation energies E a of the transformation of h-BN to the high-pressure forms of BN for different microstructures of h-BN. Defect-poor h-BN transforms to metastable wurtzitic BN (w-BN) with E a ≈ 0.3 eV/at. Defect-rich forms of h-BN transform directly to c-BN, but with a higher activation energy. It was observed that the turbostratic disorder in h-BN retards the phase transition as compared to h-BN containing corrugated basal planes and a low degree of turbostracity. The experimental results are discussed in view of the microstructure changes during the HP/HT treatment and compared to available theoretical phase transition models.